Contrasting Sensitivity of Weathering Proxies to Quaternary Climate and Sea‐Level Fluctuations on the Southern Slope of the South China Sea. Issue 24 (18th December 2021) - Zhong, Yi; Wilson, David J.; Liu, Jiabo; Wan, Shiming; Bao, Rui; Liu, Jianxing; Zhang, Yanan; Wang, Xuesong; Liu, Yuanhao; Liu, Xiaoyu; Zhao, Ying; Li, Shiying; et al.
Abstract: Tropical marginal seas host important sedimentary archives that may be exploited to reveal past changes in continental erosion, chemical weathering, and ocean dynamics. However, these records can be challenging to interpret due to the complex interactions between climate and particulate transport across ocean margins. For the southern South China Sea over the last 90 Kyr, we observe a contrasting temporal relationship between the deposition of clay minerals and magnetic minerals, which were associated with two different hydrodynamic modes. Fine‐grained clay minerals can be carried in suspension by ocean currents, leading to a rapid response to regional climate‐driven inputs. In contrast, changes in magnetic mineralogy were linked to glacial‐interglacial sea level variability, from which we infer a control by bedload transport and resuspension. Overall, this study indicates that the transfer pathways and mechanisms imparted by varying hydrodynamic conditions exert a substantial influence on the distribution of terrigenous material in continental margin sediments. Plain Language Summary: Sediments that accumulate in the ocean along continental margins contain the minerals that were eroded and transported by rivers on the nearby land masses. Past changes in the composition of such sediments can be used to reconstruct the history of physical erosion and chemical weathering on the continents, but can also be affected by ocean dynamics over orbital and millennial timescales. Here, clay mineralogy, sediment grain size, and rock magnetic signatures are measured in a core from the continental slope of the southern South China Sea, spanning the last 90 thousand years. Differences between the clay mineral and magnetic records, which are linked to finer and coarser sediment fractions respectively, indicate that specific mechanisms and timescales influenced sediment transport to the core site. This depositional framework must be considered when interpreting the timing of changes in weathering and erosion proxies hosted in sediment records from marginal seas. Specifically, fine‐grained clay minerals may reveal a rapid response to continental weathering changes, whereas the magnetic records are influenced by the transport of denser coarser‐grained minerals under the influence of sea level change. In addition, this framework could potentially serve as an indicator of past sea level change on wide continental shelves. Key Points: In the southern South China Sea, clay mineralogy responds rapidly to climate‐driven changes in inputs on orbital timescales Magnetic content within the coarser and denser fraction is influenced by sea level change, through bedload and resuspension transport This depositional framework may serve as a guideline for evaluating sea level change on wide continental shelves over orbital timescales